A Causal Loop Diagram of Banyumas Tourism Projection with Transportation System Improvement - Arini, Ratih Windu; Hidayatuloh, Syarif; Ikasari, Diniary; Herdianto, Bachtiar; Putra, Firmansyah Isrofil; Sari, Sarah Karenina (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
Banyumas is one of the famous tourist destinations in Central Java with its natural attractions. Tourism growth in Banyumas requires capable and sustainable transportation infrastructure. However, current policies and investments in Banyumas are inappropriate for developing transportation and tourism infrastructure that creates non-significant impact. Therefore, the development of tourism projection should consider environmental, social, economics, and technology interrelated in developing transportation and tourism infrastructure issues. The tourism supply chain has a unique structure that is different from typical supply chains with high complexity because many stakeholders are involved. This research aims to project Banyumas tourism development with the impact of transportation system improvement. This conceptual model was developed from literature reviews and other necessary sources, and then validated by experts. The conceptual model examines the relationship between variables involved in the tourism supply chain and transportation system in Banyumas that can be developed into a quantitative model using Causal Loop Diagram, an initial stage of system dynamics. This model used to analyze the behavior of visitor projection of the Banyumas tourism supply chain system in Indonesia.